A Quasi-Input-Output model to improve the estimation of emission factors for purchased electricity from interconnected grids. (15th August 2017) - Qu, Shen; Wang, Hongxia; Liang, Sai; Shapiro, Avi M.; Suh, Sanwong; Sheldon, Seth; Zik, Ory; Fang, Hong; Xu, Ming
Graphical abstract: Highlights: A new method is proposed to measure emission factors of electricity consumption. Comparisons with previous methods show significant improvement. A case study is conducted to demonstrate the method. Our method can be applied to measure other impacts of electricity consumption. Abstract: Estimating the embodied emissions in electricity has been a challenge due to the interconnectedness of electrical grids. Previous studies use a variety of methods that are often inaccurate or difficult to implement, lacking a standardized tool. We propose a method adapted from the economic input-output theory, which we term as "Quasi-Input-Output (QIO)" model, to evaluate embodied emissions in purchased electricity. The method takes into account the difference between the natures of trade in electricity and in goods and services, able to capture the effects of both direct and higher-order electricity transfers in the network. We use the Eurasian Continent grid network as a case, identifying regions where inter-grid electricity transfers, both direct and high-order, have sizable impacts on estimated emission factors of purchased electricity. Overall, while ignoring electricity trade can result in errors in embodied emissions estimation, directly adjusting for electricity trade (neglecting higher-order trade) tends to generate inaccuracies in the opposite direction. Our model can be potentially applied as a standard tool for the accounting of embodied emissions in purchased electricity in inter-grid electricity trade systems. It also provides a foundation for further applications of input-output theory in the analysis of demand-side drivers for environmental impacts of interconnected grids.